Bruxism and TMD: What do Dentists and Physiotherapists know about? (Research, Society and Development, 2022)
Bruxism is a frequent motor habit in the population, currently divided into awake and sleep bruxism. Temporomandibular disorders (TMD) are a group of condition that involves the chewing muscles, the TMJ and associated structures. Both concepts are often mistaken or misunderstood among health professionals and, thus, misdiagnosed and treated. The treatment of these disorders is still a matter of discussion by several health professionals, in view of their multidisciplinary character. Objvective: The aim of this article is to evaluate the knowledge about the concepts and treatment adopted by dentists and physiotherapists, as well as the interdisciplinary interaction between the two areas. Methods: The evaluation was made through a questionnaire and the data obtained was computed, compared and analyzed statistically. Results/conclusion: The study demonstrated that, despite understanding the importance of multidisciplinarity, there is still a lack of knowledge about possible treatment options and concepts.